Penguatan SistemKeamananGudang Allefix: Evaluasi Kelistrikan dan CCTV - Wibisono, Argo Aflah; suhirwan, suhirwan; Rifandi, Safriudin (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2024)
Security of electrical systems and CCTV constitutes a critical aspect in maintaining public safety, particularly amid rising theft cases exploiting infrastructure security gaps. This study aims toevaluate the ef ectiveness of the security system implemented by